Influence of drill parameters on bone temperature and necrosis: A FEM modelling and in vitro experiments - Sezek, S.; Aksakal, B.; Karaca, F. (Elsevier, 2012)
During drilling of bone, excessive heat may cause thermonecrosis and this weakens the purchase of surgically placed screws and pins thus reduces the success of subsequent fixation and implantation process. In order to minimise the problems caused by high temperature (above 45 degrees C) in bone drilling operations, it is necessary to operate with optimum cutting and drilling parameters. This study analysis the temperature changes during cortical bone drilling for different parameters such as drill rotation speed, feed-rate, drill diameter, drill force, bone mineral density and bone sex via the finite element method, FEM. The analysis have been validated by in vitro experiments using fresh calf cortical bones. Analytical and experimental results showed that the safe drilling parameters and drill temperatures can be estimated. To avoid thermal necrosis, the safe drilling zones (below 45 degrees C) have been determined for various drill parameters during drilling of fresh cortical bones. Temperature increased 10% with 12% increase in bone mineral density and the safe drill parameters obtained to be 370 rpm drill speed, 70 mm/min feed rate and 140 N drill force. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Orthopaedics; Bone drilling; Thermal necrosis; FEM